2004
DOI: 10.1016/s0006-3495(04)74139-9
|View full text |Cite
|
Sign up to set email alerts
|

Single-Molecule Imaging of the H-Ras Membrane-Anchor Reveals Domains in the Cytoplasmic Leaflet of the Cell Membrane

Abstract: In the last decade evidence has accumulated that small domains of 50-700 nm in diameter are located in the exoplasmic leaflet of the plasma membrane. Most of these domains supposedly consist of specific sets of lipids and proteins, and are believed to coordinate signal transduction cascades. Whether similar domains are also present in the cytoplasmic leaflet of the plasma membrane is unclear so far. To investigate the presence of cytoplasmic leaflet domains, the H-Ras membrane-targeting sequence was fused to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
147
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 140 publications
(177 citation statements)
references
References 42 publications
30
147
0
Order By: Relevance
“…Data on CAAX distribution support that~40% of the molecules were organized into clusters. In our previous study, using single-molecule tracking, we observed that 40% of CAAX in live cells were undergoing confined diffusion, whereas the remaining 60% were freely diffusing in the plane of the membrane (40). We suggested that this was related to membrane confinement of the membrane anchor, CAAX.…”
Section: Discussionmentioning
confidence: 86%
“…Data on CAAX distribution support that~40% of the molecules were organized into clusters. In our previous study, using single-molecule tracking, we observed that 40% of CAAX in live cells were undergoing confined diffusion, whereas the remaining 60% were freely diffusing in the plane of the membrane (40). We suggested that this was related to membrane confinement of the membrane anchor, CAAX.…”
Section: Discussionmentioning
confidence: 86%
“…One line of evidence comes from data acquired by electron microscopy methods (Plowman et al 2005;Prior et al 2003). The dynamics of Ras in the plasma membrane have also been measured by single Xuorophore tracking (SFT) (Lommerse et al 2003(Lommerse et al , 2005Murakoshi et al 2004) and with Xuorescence recovery after photobleaching (FRAP) (Niv et al 1999(Niv et al , 2002. According to these data, H-Ras clusters into cholesterol dependent nanoscale domains in its inactive GDP-bound state.…”
Section: Signaling Via Protein Clusters In the Plasma Membranementioning
confidence: 99%
“…It is important to stress, however, that these are just examples among many applications of single-molecule methods to many areas of biology, which include probing the dynamics and folding of proteins (11-16) and nucleic acids (9,17,18), the function of molecular motors (19)(20)(21)(22), the motions of proteins in membranes (23)(24)(25)(26), and viral infection (27,28).…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%